How God works : the science behind the benefits of religion - DeSteno, David (Simon & Schuster, 2021)
"Drawing on a wealth of new evidence, pioneering research psychologist David DeSteno shows why religious practices and rituals are so beneficial to those who follow them - and to anyone, regardless of their faith (or lack thereof)"--